2022
DOI: 10.3389/fonc.2022.835581
|View full text |Cite
|
Sign up to set email alerts
|

Case Report Series: Aggressive HR Deficient Colorectal Cancers Related to BRCA1 Pathogenic Germline Variants

Abstract: ObjectiveThe link between BRCA1 and homologous recombination deficiency (HRD) in cancer has gained importance with the emergence of new targeted cancer treatments, while the available data on the role of the gene in colorectal cancer (CRC) remain contradictory. The aim of this case series was to elucidate the role of known pathogenic BRCA1 variants in the development of early-onset CRC.DesignPatients were evaluated using targeted next generation sequencing, exome sequencing and chromosomal microarray analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Homologous recombination deficiency (HRD) can be assessed by the HRD score, which is a combination of homologous recombination deficiency, telomeric-allelic imbalance, and large-scale state transitions. One study reported that BRCA1 variants can be involved in CRC development through HRD and suggested that young patients with a history of microsatellite-stable colorectal cancer could be considered for BRCA1 screening (Freire et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Homologous recombination deficiency (HRD) can be assessed by the HRD score, which is a combination of homologous recombination deficiency, telomeric-allelic imbalance, and large-scale state transitions. One study reported that BRCA1 variants can be involved in CRC development through HRD and suggested that young patients with a history of microsatellite-stable colorectal cancer could be considered for BRCA1 screening (Freire et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, due to the still relative low occurrence of such germline variants, large numbers of CRC cases, that undergo extensive multigene panel testing as well as immunohistochemical staining for all four MMR proteins, would be extremely beneficial to study this relationship. Such pathogenic germline variants in HRR genes like BRCA1 should always be considered especially in young CRC cancer patients ( 57 ). However, all our patients with MLH1 - /PMS2 - /MSH6 - cancers were over 60 years of age at time of diagnosis and did not have a familiar history suspicious for cancer predisposing syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have found the presence of variants in BRCA1 and BRCA2 : in a total of 450 patients with early onset colorectal cancer, four variants were identified in BRCA1 and one variant in BRCA2 [ 44 ]; in 1260 individuals with a family history of LS, 8% had variants in these genes [ 45 ]; and in a cohort of 961 endometrial cancer patients, 1.04% presented with a PV [ 46 ]. PVs in BRCA1 and BRCA2 are classically associated with hereditary breast and ovarian cancer syndromes [ 47 ]. Colorectal cancer is not included in the BRCA1/2 tumor spectrum; published guidelines do not recommend increased detection of this type of neoplasm in carriers of mutations in these genes.…”
Section: Discussionmentioning
confidence: 99%